The Relationship between Intrinsic Motivation, Job Demand and Burnout - Suriani, Mohamad (2010)
This study aims to investigate the relationship between intrinsic motivation, job demand and burnout among hotel employees. The relationship between those variables are predicted based on relevant literature, and are tested using survey results from 121 of star-rated hotel employees in Kuala Rompin, Pahang. The Pearson Correlation matrix test is used to test the relationship between intrinsic motivation and burnout, and the relationship between job demand and burnout. An independent sample t-test and one-way ANOVA were conducted in order to determine the significant differences between demographic factors and burnout. Two of 3 hypotheses were supported and the results suggest that intrinsic motivation and job demand plays a significant role in burnout. Besides in determining the differences between demographic factors and burnout, the result shows that gender, race, marital status, employment level, highest qualification and organizational tenure was insignificantly related to burnout. As the suggestion, management should provide the extrinsic reward and social support to the employees in order to mitigate the harmful effects of burnout.